Saccharomyces cerevisiae Catalyzed Cyclocondensation Reaction: Synthesis of Pyrazoline. (25th October 2016) - Punyapreddiwar, Nitesh D.; Wankhade, Atul V.; Zodape, Sangesh P.; Pratap, Umesh R.
Abstract : A simple, efficient, and environment friendly method has been developed for the synthesis of pyrazoline by the cyclocondensation of chalcones and hydrazine hydrate using very cheaper catalyst, baker's yeast ( Saccharomyces cerevisiae ). The 3, 5-diphenyl pyrazolines are synthesized in moderate to good yield. The method also overcomes drawbacks of the previous pyrazoline synthetic methods and provides a new efficient route to 3, 5-diphenyl pyrazoline derivatives.